2014
DOI: 10.1089/lap.2014.0418
|View full text |Cite
|
Sign up to set email alerts
|

A New Exploration for Gallbladder Polyps: Gallbladder Polypectomy by Endolap Technique

Abstract: Gallbladder polyps are most commonly treated with cholecystectomy, which is associated with various complications. For benign disease, preserving the gallbladder is preferable. Since 1994, we have been exploring percutaneous polypectomy and have recently developed an improved new technique. This study reports a new endoscopic-laparoscopic (Endolap) technique for the removal of polyps and the preservation of the gallbladder. Nine Chinese mini-pigs were used to observe mucosal regeneration. Microwaves of 50-70 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Secondly, the lesion can be completely removed to reduce gallbladder cancer risk, and the pathological diagnosis of polyps can be obtained to develop further treatment or follow-up strategies. Thirdly, compared with traditional laparoscopic-assisted gallbladder-preserving polypectomy [ 13 , 22 , 23 ], the main advantage of E-NOTES is that the umbilical cord is the weakest part of the abdominal wall, and transumbilical puncture can not only reduce the injury of the abdominal wall, but also relieve the pain of the surgical wound. Furthermore, the 2–4 incisions in the abdomen of the traditional laparoscopic surgery can be transformed into a small incision of 10 mm in the umbilical cord.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the lesion can be completely removed to reduce gallbladder cancer risk, and the pathological diagnosis of polyps can be obtained to develop further treatment or follow-up strategies. Thirdly, compared with traditional laparoscopic-assisted gallbladder-preserving polypectomy [ 13 , 22 , 23 ], the main advantage of E-NOTES is that the umbilical cord is the weakest part of the abdominal wall, and transumbilical puncture can not only reduce the injury of the abdominal wall, but also relieve the pain of the surgical wound. Furthermore, the 2–4 incisions in the abdomen of the traditional laparoscopic surgery can be transformed into a small incision of 10 mm in the umbilical cord.…”
Section: Discussionmentioning
confidence: 99%
“…The gallbladder-emptying function was expressed by the gallbladder emptying index: (fasting volume—postprandial volume)/ fasting volume × 100%. The gallbladder-emptying function was good, acceptable, poor respectively when the gallbladder emptying index were more than 50%, 33.3% to 50%, less than 33.3% [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the surgical technique of laparoscopic-choledochoscopic polypectomy has been reported to remove polyps but preserve the gallbladder [5, 9]. Preservation of a functional gallbladder is important for humans.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive gallbladder-preserving cholecystolithotomy (GPC) has been applied in the treatment of patients with a small number of stones, with little morbidity and few recurrences [7, 8]. A surgical technique of laparoscopic-choledochoscopic polypectomy has been reported to remove polyps and to preserve the gallbladder [5, 9]. However, the long-term outcome of this technique needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, suggested doing polypectomy only, without cholecystectomy by using endolap (endoscopic laparoscopic technique) through experimental laboratory, which was successful and safe [50].…”
Section: Methodsmentioning
confidence: 99%